Plant Growth Inhibitory Activity of Hibiscus sabdariffa Calyx and the Phytotoxicity of Hydroxycitric Acid Lactone - Tugba, G.I.O.; Appiah, K.S.; Akalin, E.; Yoshiharu, F. (My University, 2023)
Weeds pose major constraints in crop production. The use of allelochemicals and allelopathic species can provide an effective alternative for sustainable weed management. In a previous study that evaluated the allelopathic activity of wild and cultivated plants in Turkey, Hibiscus sabdariffa demonstrated the strongest inhibitory potential. This study aimed to estimate the phytotoxic influence of the H. sabdariffa water crude extracts on Lactuca sativa L. in a bioassay experiment. High-performance liquid chromatography (HPLC) analysis was used to identify two major compounds, hydroxycitric acid lactone and hydroxy citric acid, and their plant growth inhibitory activities were evaluated by bioassays. Hydroxycitric acid lactone had a stronger growth inhibitory activity on L. sativa L. and was estimated as a major allelochemical in H. sabdariffa calyx. The high concentration (16.7% of the dry weight of the calyx) and strong inhibitory effect (EC50, 73.7 ppm) of the hydroxycitric acid lactone could demonstrate the growth inhibitory activity of the H. sabdariffa calyx extract. This study showed that hydroxycitric acid lactone, a major compound in the calyx of Hibiscus sabdariffa, is a plant growth inhibitor.
Research Article
Keywords: phytotoxicity; Hibiscus sabdariffa calyx; hydroxycitric acid lactone; hydroxycitric acid; specific activity; total activity